1993
DOI: 10.1128/aac.37.9.1816
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo disposition and metabolism of 3'-deoxy-2',3'-didehydrothymidine

Abstract: The disposition and metabolic fate of 3'-deoxy-2',3'-didehydrothymidine (D4T) were 3'-Deoxy-2',3'-didehydrothymidine (D4T) is a thymidine analog with potent anti-human immunodeficiency virus activity in vitro comparable to that of 3'-azido-3'-deoxythymidine (AZT) (23,24). Previous studies on D4T metabolism, by several groups including our own, have demonstrated that D4T is sequentially phosphorylated by cellular enzymes to D4T-TP, the active form which competitively inhibits TTr incorporation by human immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
7
21
0
Order By: Relevance
“…The route of elimination in humans is in concurrence with the findings in mice, rats, and monkeys (Russell et al, 1990;Cretton et al, 1993;Kaul and Dandekar, 1993;Kaul et al, 1999). The extent of absorption and oral bioavailability of stavudine in humans was at least 95 and 67%, respectively, based on urinary recovery values of TRA and stavudine.…”
Section: Disposition Of Stavudine In Humanssupporting
confidence: 66%
See 2 more Smart Citations
“…The route of elimination in humans is in concurrence with the findings in mice, rats, and monkeys (Russell et al, 1990;Cretton et al, 1993;Kaul and Dandekar, 1993;Kaul et al, 1999). The extent of absorption and oral bioavailability of stavudine in humans was at least 95 and 67%, respectively, based on urinary recovery values of TRA and stavudine.…”
Section: Disposition Of Stavudine In Humanssupporting
confidence: 66%
“…14 C]stavudine, [4- 14 C]stavudine, or [5-3 H]stavudine (all labels on the thymidine moiety) showed that the compound was well absorbed (Russell et al, 1990;Cretton et al, 1993;Kaul and Dandekar, 1993;Kaul et al, 1999). The recovery of the drug in excreta varied in animals, with the majority of the dose recovered in the urine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because only AZT and d4T (two thymidine analogues) increased the levels of plasma ketone bodies, whereas ddI (an inosine analogue) or 3TC and ddC (two cytidine analogues) had no ketogenetic effects, we examined whether the ketogenetic effects of AZT and d4T could be reproduced by 〉〈I〉〈, a ␤-amino acid generated during thymine catabolism (1,19). Plasma ketone bodies were thus assessed in mice treated with 〉〈I〉〈 (10 or 100 mg/kg/day) for 2 weeks and fasted for the (Fig.…”
Section: Vol 47 2003 Mitochondrial Effects Of Nucleoside Analogues mentioning
confidence: 99%
“…Intracellularly, it is sequentially phosphorylated to produce its active form, stavudine-5'-triphosphate (d4T-TP) (11). In a study using monkeys and isolated rat hepatocytes, the degradation of stavudine was detected in thymine (12) and the d4T-TP derivative, with subsequent production of beta aminoisobutyric acid (BAI-BA) (13) (Cretton et al, 1993). The glucuronide metabolite (14) of stavudine was found in the urine of monkeys but has remained controversial (Schinazi, et al, 1990).…”
Section: Nucleoside Analogue Reverse Transcriptase Inhibitors (Nrtis)mentioning
confidence: 99%